Counterselection and Co-Delivery of Transposon and Transposase Functions for Sleeping Beauty-Mediated Transposition in Cultured Mammalian Cells. Issue 6 (12th September 2005) - Converse, Andrea D.; Belur, Lalitha R.; Gori, Jennifer L.; Liu, Geyi; Amaya, Felipe; Aguilar-Cordova, Estuardo; Hackett, Perry B.; McIvor, R. Scott
Abstract : Sleeping Beauty (SB) is a gene-insertion system reconstructed from transposon sequences found in teleost fish and is capable of mediating the transposition of DNA sequences from transfected plasmids into the chromosomes of vertebrate cell populations. The SB system consists of a transposon, made up of a gene of interest flanked by transposon inverted repeats, and a source of transposase. Here we carried out a series of studies to further characterize SB-mediated transposition as a tool for gene transfer to chromosomes and ultimately for human gene therapy. Transfection of mouse 3T3 cells, HeLa cells, and human A549 lung carcinoma cells with a transposon containing the neomycin phosphotransferase ( NEO ) gene resulted in a several-fold increase in drug-resistant colony formation when co-transfected with a plasmid expressing the SB transposase. A transposon containing a methotrexate-resistant dihydrofolate reductase gene was also found to confer an increased frequency of methotrexate-resistant colony formation when co-transfected with SB transposase-encoding plasmid. A plasmid containing a herpes simplex virus thymidine kinase gene as well as a transposon containing a NEO gene was used for counterselection against random recombinants ( NEO + TK +) in medium containing G418 plus ganciclovir. Effective counterselection required a recovery period of 5 days after transfection before shifting into medium containing ganciclovir to allow time for transiently expressed thymidine kinase activity to subside in cells not stably transfected. Southern analysis of clonal isolates indicated a shift from random recombination events toward transposition events when clones were isolated in medium containing ganciclovir as well as G418. We found that including both transposon and transposase functions on the same plasmid substantially increased the stable gene transfer frequency in Huh7 human hepatoma cells. The results from these experiments contribute technical and conceptual insight into the process of transposition in mammalian cells, and into the optimal provision of transposon and transposase functions that may be applicable to gene therapy studies.